Feline Infectious Peritonitis - Diagnostic and Therapeutic Approach - Gurzoni Cucolicchio, Marcela; Cristina Silva, Beatriz; Miranda Passos, Pedro Henrique; Martins Oliveira, Iago (Acta Scientiae Veterinariae, 2025)
Background: Feline infectious peritonitis (FIP) is one of the most significant infectious diseases affecting cats worldwide. Although the exact etiology remains uncertain, the disease is frequently linked to factors such as stress, immunosuppression, and heightened susceptibility to infections. The clinical presentation of FIP is often non-specific during the initial stages, making early diagnosis challenging. Common early signs include anorexia, lethargy, intermittent fever, lymphadenopathy, jaundice, and weight loss, particularly in kittens, which may also struggle to gain weight appropriately. This case report underscores the critical importance of employing a comprehensive diagnostic approach combined with meticulous follow-up during FIP treatment. Case: A 2-year-old neutered cat of no specific breed, weighing 4.8 kg, presented with clinical signs including lethargy, hypodipsia, anorexia, and significant progressive weight loss, amounting to over 1.5 kg within a month. On physical examination, notable findings included mild jaundice, approximately 3% dehydration, and a slightly elevated rectal temperature of 39.4°C. Palpation of the abdomen revealed suspicion of free fluid, which was confirmed by a positive fluid wave test. Other clinical parameters were within normal limits. To investigate differential diagnoses for ascites and jaundice, an extensive panel of tests and procedures was conducted. These included a complete blood count (CBC), creatinine, urea, alkaline phosphatase, alanine aminotransferase, gamma-glutamyl transferase, total bilirubin and fractions, total protein fractions, glucose, fructosamine, feline-specific pancreatic lipase, and rapid ELISA tests for FIV and FeLV. Molecular diagnostics were also performed, including qPCR for FIV, FeLV, and Mycoplasma spp. Additional analyses included urinalysis, the urine protein-to-creatinine ratio, abdominal ultrasound, Doppler echocardiography, and an electrocardiogram. Peritoneal effusion was further examined through biochemical and cytological assessments, such as the Rivalta test, FCoV qPCR, microbiological culture, and antimicrobial sensitivity testing. Based on clinical suspicion of FIP, treatment commenced with injectable GS-441524, later transitioned to oral capsules after 30 days. To ensure thorough disease management and minimize recurrence risk, follow-up included laboratory and imaging evaluations on days 10, 30, 60, and 80 of treatment. The therapeutic protocol, based on nucleoside analog GS-441524, adhered to established practices in veterinary literature and demonstrated a highly satisfactory outcome. Discussion: FIP accounts for an estimated 0.3%-1.4% of feline fatalities in veterinary settings, solidifying its status as a critical infectious disease among cats. A presumptive diagnosis of FIP relies on integrating multiple facets, including the animal's history, epidemiological risk factors, clinical manifestations, exclusion of other differential diagnoses, and findings from laboratory and imaging studies. Despite the diagnostic challenges, initiating GS-441524 treatment without a definitive diagnosis is justified due to its rapid therapeutic effects. Ongoing patient monitoring throughout the treatment course significantly enhances the likelihood of a positive prognosis. Case reports such as this play a vital role in expanding the collective knowledge about FIP, particularly regarding its clinical progression, diagnostic strategies, and optimal therapeutic approaches, contributing to improved outcomes for affected feline patients. Keywords: cats, diagnosis, FIP, GS-441524. Título: Peritonite Infecciosa Felina - abordagem diagnóstica e terapêutica. Descritores: gatos, diagnóstico, GS-441524, PIF.